Sexually transmitted infections among UK street-based sex workers. Issue 1 (27th September 2007) - Creighton, S; Tariq, S; Perry, G
Abstract : Background: Female sex workers are a heterogeneous group and recent reports of declining incidence of sexually transmitted infections (STIs) do not apply to all populations. This is an observational study of street-based sex workers attending an inner-London genitourinary (GU) clinic between 1 July 2006 and 31 January 2007. Methods: In July 2006 the local sex worker outreach project developed a weekly drop-in for street-based sex workers. From the drop-in, sex workers were fast tracked to attend a range of dedicated health services, including the GUM clinic. Results: The outreach team made contact with 120 street-based sex workers in the borough. 40 of these attended the drop-in and 25 attended the GU clinic. 8 had tuberculosis. There were frequent reports of recent recreational drug use, unprotected sex with clients and no reliable contraception. 7 were pregnant, 6 were HIV positive and 12 had positive syphilis serology. A further 17 STIs were identified. Conclusions: There was a high frequency of HIV, syphilis, other bacterial STIs and unwanted pregnancy among sex workers attending this clinic. There were considerable amounts of other physical ill health in this group, with frequently reported risky sexual behaviour. This study demonstrates the need for targeted development work to meet the multifactorial needs of these women.